Is there still room to explore cyclodextrin glycosyltransferase-producers in Brazilian biodiversity? - ANDREA C.S.M GOMES; SAMUEL R. DOS SANTOS; MAYCON C. RIBEIRO; PEDRO V.L. CRAVO; JOSÉ DANIEL G. VIEIRA; KEILI M.C. DE SOUZA; ANDRE C. AMARAL (Anais da Academia Brasileira de Ciências)
ABSTRACT In the present work, different Brazilian biomes aiming to identify and select cyclodextrin glycosyltransferase-producer bacteria are explored. This enzyme is responsible for converting starch to cyclodextrin, which are interesting molecules to carry other substances of economic interest applied by textile, pharmaceutical, food, and other industries. Based on the enzymatic index, 12 bacteria were selected and evaluated, considering their capacity to produce the enzyme in culture media containing different starch sources. It was observed that the highest yields were presented by the bacteria when grown in cornstarch. These bacteria were also characterized by sequencing of the 16S rRNA region and were classified as Bacillus, Paenibacillus, Gracilibacillus and Solibacillus.